Answer:
y = - x + 1
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Calculate m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 1, 2) and (x₂, y₂ ) = (4, - 3)
m = [tex]\frac{-3-2}{4+1}[/tex] = [tex]\frac{-5}{5}[/tex] = -1, hence
y = - x + c ← is the partial equation
To find c substitute either of the 2 points into the partial equation
Using (- 1, 2), then
2 = 1 + c ⇒ c = 2 - 1 = 1
y = - x + 1 ← equation in slope- intercept form
The equation is y = –x + 1.
To find the slope-intercept form of a line passing through two points, calculate the slope using the given points and then use one point to find the y-intercept. The final equation for the line through the points (–1, 2) and (4, –3) is y = –x + 1.
To write an equation in slope-intercept form for the line passing through the points (–1, 2) and (4, –3), we first need to calculate the slope (m) using the formula
m = (y2 - y1) / (x2 - x1). Plugging in our points gives us m = (–3 – 2) / (4 – (–1)) = –5 / 5 = –1. Now that we have the slope, we can use one of the points to find the y-intercept (b). Using the point (–1, 2) and the slope-intercept formula y = mx + b, we plug in the values to get 2 = (–1)×(–1) + b, simplifying to 2 = 1 + b, which yields b = 1. Thus, the equation is y = –x + 1.
On a horizontal number line, 6 is located to the
of -4. So, -6 is
than-4
On a horizontal number line, -6 is located to the (left) of -4. So, -6 is (less than) 4.
Answer:
On a horizontal number line, -6 is located to the (left) of -4. So, -6 is (less than) 4.
Step-by-step explanation:
Simplify: 3x – 5 + 23x – 9
Simple form of equation 3x – 5 + 23x – 9 = 26x-14
Further ExplanationLinear Equation in One Variable is an equation that has a variable and the exponent number is one.
Can be stated in the form:
[tex] \large {\boxed {\bold {ax = b}} [/tex]
or
ax + b = c, where a, b, and c are constants, x is a variable
Whereas Linear Equation in two Variable is a linear equation that has 2 variables and the exponent is one
Can be stated in the form:
[tex] \large {\boxed {\bold {ax + bx = c}}} [/tex]
x, y = variable
There are several ways to solve an equation
• Add / Subtract / divide / multiply the same value on both sides
• Combine like terms
• Factoring
• Expanding
Like terms are terms whose variables and their exponents are the same.
You can combine and add terms
The algebraic form of 3x - 5 + 23x - 9 is a Linear Equation in One Variable, can be simplified:
• 1. Combine like terms
(3x + 23x) + (-5 - 9)
• 2. Add like terms:
26x -14
Learn morean algebraic expression
brainly.com/question/20988
brainly.com/question/2285423
brainly.com/question/2241589
[tex]\(3x - 5 + 23x - 9\)[/tex] simplifies to [tex]\(26x - 14\).[/tex]
To simplify the expression [tex]\(3x - 5 + 23x - 9\)[/tex], we can combine like terms
[tex]\[3x - 5 + 23x - 9 = (3x + 23x) + (-5 - 9)\][/tex]
[tex]\[= 26x - 14\][/tex]
What is the point-slope form of a line that has a slope of 5 and passes through point (-7, 2)?
1.)02-1-27-x)
2.)o 7-y= (2-0)
3.)9-7= (x-2)
4.)y-2= 2(x+(+7)
The point slope of the line that passes through the points (-7, 2) and having a slope of 5 is y - 2 = 5 (x + 7).
What is Slope?Slope of a line is the ratio of the change in y coordinates to the change in the x coordinates of two points given.
Given that,
Slope of a line = 5
A point on the line = (-7, 2)
Point slope of a line having a slope of m and passing through a point (x', y') is,
y - y' = m(x - x')
Substituting the given slope and point,
y - 2 = 5 (x - -7)
y - 2 = 5 (x + 7)
Hence the required form of the line is y - 2 = 5 (x + 7).
Learn more about Point Slope form here :
https://brainly.com/question/29054476
#SPJ7
Simplify 3(7-3) the second power -4(6+2)
Answer:
112
Step-by-step explanation:
3(7-3) = 3 x 4 = 12
12^2 = 144
144 -4(6+2)
144-4(8)
144-32
112
[tex]\bf \stackrel{\mathbb{P~E~M~D~A~S}}{3(7-3)^2-4(6+2)}\implies 3(\stackrel{\downarrow }{4})^2-4(\stackrel{\downarrow }{8})\implies 3(\stackrel{\downarrow }{16})-4(8) \\\\\\ \stackrel{\downarrow }{48}-4(8)\implies 48-\stackrel{\downarrow }{32}\implies 16[/tex]
Need help here, please.
Identify the vertex of y = x2 + 4x + 5.
A. (0,0)
B. (–2,9)
C. (–2,1)
D. (4,5)
Answer:
Option C is correct.
Step-by-step explanation:
y = x^2+4x+5
We need to find the vertex of the above equation.
The above equation represents the parabola.
The slope of parabola can be found by taking derivative of the given equation
dy/dx = 2x+4
The slope of the parabola at the vertex is zero SO,
2x+4 = 0
2x = -4
x = -4/2
x = -2
Putting value of x =-2 to find the value of y
y = x^2+4x+5
y =(-2)^2+4(-2)+5
y = 4-8+5
y =9-8
y = 1
So, the vertex is (-2,1)
Option C is correct.
Can someone solve these?
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept
[tex]61)\ m=3,\ b=-2\\\\\boxed{y=3x-2}\\\\62)\ m=\dfrac{4}{5},\ b=4\\\\\boxed{y=\dfrac{4}{5}x+4}\\\\63)\ m=-\dfrac{7}{4},\ b=-3\\\\\boxed{y=-\dfrac{7}{4}x-3}\\\\64)\ m=-\dfrac{3}{4},\ b=-2\\\\\boxed{y=-\dfrac{3}{4}x-2}[/tex]
Calculate the arc length of GH in terms of pi.
Answer:
10π/3 mm
Step-by-step explanation:
Arc length is:
s = rθ × π/180
where r is the radius and θ is the angle in degrees.
Here, r = 10 mm and θ = 60°.
s = (10) (60) (π/180)
s = 10π/3
Another way to calculate it is to find the entire circumference then divide by 6, since 60° is one-sixth of 360°.
What is the measure of EFG in 0 0 below?
O
A. 240°
O
B. 120°
O
C. 300
O
D. 60°
Answer:
C. 300
Step-by-step explanation:
EFG and EG is the total distance around the circle
EFG + EG = 360 degrees
EFG + 60 = 360
Subtract 60 from each side
EFG +60-60 = 360-60
EFG = 300
Answer:
C. [tex]\widehat{GFE}=300^{\circ}[/tex]
Step-by-step explanation:
We have been given an image of a circle. We are asked to find the measure of major arc EFG for our given circle.
First of all, we will find measure of arc GE.
We know that the measure of central arc is equal to its subtended arc. The measure of arc GS will be equal to measure of central angle GOE.
Since measure of central angle GOE is 60 degree, so measure of arc GE is 60 degrees as well.
We know that the circumference of circle is equal to 360 degrees. So we can set an equation as:
[tex]\widehat{GE}+\widehat{GFE}=360^{\circ}[/tex]
[tex]60^{\circ}+\widehat{GFE}=360^{\circ}[/tex]
[tex]60^{\circ}-60^{\circ}+\widehat{GFE}=360^{\circ}-60^{\circ}[/tex]
[tex]\widehat{GFE}=300^{\circ}[/tex]
Therefore, the measure of arc GFE is 300 degrees and option C is the correct choice.
What is the domain of the function shown in the mapping?
{x | x = -5, -3, 1, 2, 6}
{yly=-9, -6, 0, 2, 4}
{x | x = -9, -6, -5, -3, 0, 1, 2, 4, 6}
{yly = -9, -6, -5, -3, 0, 1, 2, 4, 6}
The domain of the function in the mapping given is: A. {x | x = -5, -3, 1, 2, 6}.
What is the Domain of a Function?The domain of a function includes all the possible values of x (input) in a function.
The corresponding set of y-values (output) is the range of the function.
The set of x-values in the mapping are, -5, -3, 1, 2, 6.
Therefore, the domain of the function in the mapping given is: A. {x | x = -5, -3, 1, 2, 6}.
Learn more about domain of a function on:
https://brainly.com/question/10891721
What is the completely factored form of the expression 16x2 + 8x + 32?
4(4x2 + 2x + 8)
4(12x2 + 4x + 28)
8(2x2 + x + 4)
8x(8x2 + x + 24)
Answer:
[tex]8(2x^2 + x + 4)[/tex]
Step-by-step explanation:
Given:
[tex]16x^2+8x+32[/tex]We'd factor out 8:
[tex]8(2x^2 + x + 4)[/tex]
Our answer would be [tex]8(2x^2 + x + 4)[/tex]
The completely factored form of the expression 16x2 + 8x + 32 is 8(2x2 + x + 4), after factoring out the greatest common factor, 8.
The question asks for the completely factored form of the expression 16x2 + 8x + 32. To factor this expression completely, we look for a common factor in all the terms. Observing the coefficients (16, 8, and 32), we recognize that 8 is the greatest common factor (GCF). Factoring out the GCF, we get:
8(2x2 + x + 4).
This expression cannot be factored further since the quadratic inside the parentheses does not factor neatly over the integers. Thus, the completely factored form of 16x2 + 8x + 32 is 8(2x2 + x + 4).
Measure the angle and classify it as right,acute,or obtuse
Answer:
there is no picture for me to answer on
Which of the following is an odd function?
F(x)= 3x^2+x
F(x)=4x^3+7
F(x)=5x^2+9
F(x)=6x^3+2x
Answer:
[tex]\large\boxed{f(x)=6x^3+2x}[/tex]
Step-by-step explanation:
[tex]\text{If}\ f(-x)=f(x)\ \text{then}\ f(x)\ \text{is an even function.}\\\\\text{If}\ f(-x)=-f(x)\ \text{then}\ f(x)\ \text{is an odd function.}[/tex]
======================================================
[tex]f(x)=3x^2+x\\\\f(-x)=3(-x)^2+(-x)=3x^2-x\\\\f(-x)\neq f(x)\ \wedge\ f(-x)\neq-f(x)\\\\============================\\\\f(x)=4x^3+7\\\\f(-x)=4(-x)^3+7=-4x^3+7\\\\f(-x)\neq f(x)\ \wedge\ f(-x)\neq-f(x)\\\\============================\\\\f(x)=5x^2+9\\\\f(-x)=5(-x)^2+9=5x^2+9\\\\f(-x)=f(x)-\text{It's an even function}\\\\============================\\\\f(x)=6x^3+2x\\\\f(-x)=6(-x)^3+2(-x)=-6x^3-2x=-(6x^3+2x)\\\\f(-x)=-f(x)-\text{It's an odd function.}[/tex]
The function F(x)= 3x²+x is an odd function, option A is correct.
What is a function?A relation is a function if it has only One y-value for each x-value.
To determine whether a function is odd or not, we need to check if f(-x) = -f(x) for all x in the domain of the function.
Let's check the function
F(x) = 3x²+ x
F(-x) = 3(-x)² + (-x) = 3x²- x
-f(x) = -(3x² + x) = -3x² - x
Since F(-x) = -f(x), this function is odd.
The other functions are even as they satisfy f(-x)=f(x)
Hence, the function F(x)= 3x²+x is an odd function, option A is correct.
To learn more on Functions click:
https://brainly.com/question/30721594
#SPJ7
The table below shows the values of y for different values of x:
x y
0
0
1
5
2
10
3
15
Which equation shows the relationship between x and y?
Answer:
[tex]y=5x[/tex]
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
we have
For x=0, y=0 -----> the line passes through the origin
For x=1, y=5 ----> [tex]k=y/x=5/1=5[/tex]
For x=2, y=10 ----> [tex]k=y/x=10/2=5[/tex]
For x=3, y=15 ----> [tex]k=y/x=15/3=5[/tex]
so
The constant of proportionality is k=5
The table represent a direct variation
The equation is equal to [tex]y=kx[/tex]
substitute the value of k
[tex]y=5x[/tex]
19. What are the coordinates of the midpoint
of the segment with endpoints at (-3, 9) and
(10, 18)?
Answer:
[tex]\large\boxed{\left(\dfrac{7}{2},\ \dfrac{27}{2}\right)}[/tex]
Step-by-step explanation:
The formula of a midpoint of a segment AB with endpoints at A(x₁, y₁) and B(x₂, y₂):
[tex]M_{AB}\left(\dfrac{x_1+x_2}{2},\ \dfrac{y_1+y_2}{2}\right)[/tex]
We have the points (-3, 9) and (10, 18).
Substitute:
[tex]M(x,\ y)\\\\x=\dfrac{-3+10}{2}=\dfrac{7}{2}\\\\y=\dfrac{9+18}{2}=\dfrac{27}{2}[/tex]
Quadrilateral ABCD is similiar to quadrilateral EFGH. The lengths of the three longest sides in quadrilateral ABCD are 20 feet, 18 feet, and 14 feet long. If the two shortest sides of quadrilateral EFGH are 6 feet long and 5 feet long, how long is the 4th side on quadrilateral ABCD?
Answer:
The 4th side on quadrilateral ABCD is [tex]11\frac{2}{3}\ ft[/tex]
Step-by-step explanation:
we know that
If two figures are similar, then the ratio of its corresponding sides is proportional and this ratio is called the scale factor
In this problem
The corresponding sides are
ABCD EFGH
20 ft ?
18 ft ?
14 ft 6 ft
? 5 ft
The length side of 14 ft in quadrilateral ABCD is the corresponding side to the length side of 6 ft in quadrilateral EFGH
so
the scale factor from quadrilateral ABCD to quadrilateral EFGH is
[tex]6/14=3/7[/tex]
therefore
To find the length of the 4th side on quadrilateral ABCD, divide the length of the 4th side on quadrilateral EFGH by the scale factor
so
[tex]5/(3/7)=35/3\ ft[/tex]
convert to mixed number
[tex]\frac{35}{3}\ ft=\frac{33}{3}+\frac{2}{3}=11\frac{2}{3}\ ft[/tex]
7 1⁄5 – 6 2⁄5 = ?
A. 1 4⁄5
B. 4⁄5
C. 13 3⁄5
D. 1 1⁄5
Answer:
B. 4⁄5
Step-by-step explanation:
7 1⁄5
– 6 2⁄5
-----------------
We need to borrow from the 7 since 1/5 is less than 2/5
7 becomes 6 and the one becomes 5/5
6 5/5+1⁄5
– 6 2⁄5
-----------------
Combining the fraction
6 6⁄5
– 6 2⁄5
-----------------
4/5
Find the simple interest rate needed in order for an investment of $2000 to grow to an account of $5000 in 3 years
[tex]\bf ~~~~~~ \textit{Simple Interest Earned Amount} \\\\ A=P(1+rt)\qquad \begin{cases} A=\textit{accumulated amount}\dotfill & \$5000\\ P=\textit{original amount deposited}\dotfill&\$2000\\ r=rate\to r\%\to \frac{r}{100}\\ t=years\dotfill &3 \end{cases} \\\\\\ 5000=2000(1+r3)\implies \cfrac{5000}{2000}=1+3r\implies \cfrac{5}{2}=1+3r \\\\\\ 5=2+6r\implies 3=6r\implies \cfrac{3}{6}=r\implies 0.5=r\implies \stackrel{\textit{converting to percent}}{0.5\cdot 100\implies 50\%}[/tex]
Which explains whether Triangle FGH is congruent to Triangle FJH?
Answer:
The correct answer is third option
They are not congruent, because only one pair of corresponding sides is congruent.
Step-by-step explanation:
From the figure we can see that, two isosceles triangles.
ΔFGH and ΔFJH
We get FG = GH and FJ = HJ
And side FH is common for both the triangles.
We can not say these two triangles are congruent.
Therefor the correct answer is third option
They are not congruent, because only one pair of corresponding sides is congruent.
Final answer:
The congruency between Triangle FGH and Triangle FJH can be considered through Desargues's theorem, which relates congruency to parallel sides and intersecting vertex connections, and similarity can also be established by the AAA theorem, which involves congruent corresponding angles.
Explanation:
To determine whether Triangle FGH is congruent to Triangle FJH, one would need to employ the principles of Desargues's theorem, which states that if two triangles have their corresponding vertices connected by lines that meet at a point, and if the corresponding sides of the triangles are parallel, then the triangles are congruent. The information given suggests multiple instances where triangles are similar or congruent based on the congruency of angles or parallelism of lines, as dictated by the aforementioned theorem. For example, in the triangles ABC and FCE mentioned, the similarity is confirmed via the Angle Angle Angle (AAA theorem) because all corresponding angles of the triangles are congruent, which is a direct consequence of the vertical angles property and the alternate interior angles property. This similarity implies that there's a proportionality between the sides of the triangles, which could be a stepping stone in proving the congruency between Triangle FGH and Triangle FJH if similar conditions apply.
the weight of a bucket is 33/2 kg. if 1/4 of the bucket contains water weighing 21/4 kg , determine the weight of empty bucket
Answer:
15.733kg
Step-by-step explanation:
33.2 - 21.4 = 11.8
3/4 of the bucket empty is 11.8kg.
11.8 divided by 3 is 3.933. 3.933 x 4 is 15.733
What is the image of (9,-5) after a dilation with the scale factor of 2.5?
factor 125x3 + 343y3
Answer:
(5x + 7y)(25x² - 35xy + 49y²)
Step-by-step explanation:
125x³ + 343y³ ← is a sum of cubes and factors in general as
a³ + b³ = (a + b)(a² - ab + b² )
125x³ = (5x)³ ⇒ a = 5x
343y³ = (7y)³ ⇒ b = 7y
125x³ + 343y³
= (5x + 7y)((5x)² - (5x × 7y) + (7y)²)
= (5x + 7y)(25x² - 35xy + 49y²) ← in factored form
Is Erik's statement correct? Why or why not?
Yes, the solids are both cones and appear to have
the same volumes.
Yes, the area of the bases and the heights of the
cones are the same, so the volumes are equal.
O No, the heights of the cones are not the same, so
Cavalieri's principle does not apply.
Answer:
Step-by-step explanation:
No, the heights of the cones are not the same, so Cavalieri’s principle does not apply.
log5(10x-1)=log5(9x+7)
whats the final answer
Answer:
x = 8
Step-by-step explanation:
log₅ (10x − 1) = log₅ (9x + 7)
10x − 1 = 9x + 7
x = 8
i am extremely confused, can anyone help?
Answer:
So I did most of you table for you:
First blank:4
Second blank:-4
Third blank:-8
Fourth blank: Left to you: Just plug in 6 into 1/2x^2-5x+4 (I will check)
Fifth blank: Left to you: Just plug in 8 into 1/2x^2-5x+4 (I will check)
The graph is D.
Step-by-step explanation:
So they have a table to fill in and they tell you in the first row what they want you to plug in
So the table is asking us to answer this:
What is h(0),h(2),h(4),h(6), and h(8).
h(0) means to replace x with 0 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2}(0)^2-5(0)+4[/tex]
[tex]0-0+4[/tex]
[tex]0+4[/tex]
[tex]4[/tex]
So the first blank is 4 since h(0)=4.
h(2) means to replace x with 2 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2} (2)^2-5(2)+4[/tex]
[tex]\frac{1}{2} (4)-10+4[/tex]
[tex]2-10+4[/tex]
[tex]-8+4[/tex]
[tex]-4[/tex]
So the second blank is -4 since h(2)=-4.
h(4) means to replace x with 4 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2}(4)^2-5(4)+4[/tex]
[tex]\frac{1}{2}(16)-20+4[/tex]
[tex]8-20+4[/tex]
[tex]-12+4[/tex]
[tex]-8[/tex]
So the third blank is -8 since h(4)=-8
Maybe you can try the last 2 blanks in the table part. That is try computing h(6) and h(8). I will check it for you.
Now the points I have so far are (0,4) from the h(0)=4, (2,-4) from the h(2)=-4, and (4,-8) from the h(4)=-8.
I'm looking for a graph that goes through these points (0,4) , (2,-4) , and (4,-8).
By the way the only graphs that are worth looking at is C and D because they are open up. I know my curve for h(x)=1/2x^2-5x+4 should be a parabola open up because 1/2 is positive and 1/2 is the coefficient of x^2.
So Graph C has y-intercept (0,10) not (0,4) so Graph C is not right.
Graph D has y-intercept (0,4). It also goes through (2,-4) and (4,-8).
I don't know if you notice but the x-axis and y-axis are going up by two's in each graph.
What is the solution to 2h +8 > 3h - 6
Answer:
h < 14
Step-by-step explanation:
2h +8 > 3h - 6
2h - 3h > - 6 - 8
-h > -14 (multiply both sides by -1; remember to flip the inequality sign!)
h < 14
Solve the second equation.
2x - y = 8
First, solve for (-y).
--y =
Answer:
[tex]-y=-2x+8\\y=2x-8[/tex]
Step-by-step explanation:
To solve, first subtract 2x from both sides.
[tex]2x-y=8\\-y=-2x+8[/tex]
You appear to want the solution for -y, so I've included it. Given that you also want the solution for y, divide both sides by -1.
[tex]-y=-2x+8\\y=2x-8[/tex]
Answer:
- y = 8 - 2x
Step-by-step explanation:
2x - y = 8
Subtracting 2x on both sides,
=> 2x - 2x - y = 8 - 2x
=> - y = 8 - 2x
Which of the following sets of ordered pairs does not define a function? {(−1,4),(0,4),(1,4),(2,4),(3,4)} { ( − 1 , 4 ) , ( 0 , 4 ) , ( 1 , 4 ) , ( 2 , 4 ) , ( 3 , 4 ) } {(1,2),(5,6),(6,7),(10,11),(13,14)} { ( 1 , 2 ) , ( 5 , 6 ) , ( 6 , 7 ) , ( 10 , 11 ) , ( 13 , 14 ) } {(1,1),(2,2),(3,3),(4,4),(5,5)} { ( 1 , 1 ) , ( 2 , 2 ) , ( 3 , 3 ) , ( 4 , 4 ) , ( 5 , 5 ) } {(1,3),(5,2),(6,9),(1,12),(10,2)}
The set of ordered pairs that defines a function is: {(1,3),(5,2),(6,9),(1,12),(10,2)} (last option).
What is a Function?A set of ordered pairs that defines a function will have exactly one y-value that assigned to every x-value. In essence, it means none of its x-values can have two corresponding y-value.
All the sets of ordered pairs have exactly one y-value that corresponds to each of its x-value except {(1,3),(5,2),(6,9),(1,12),(10,2)}, which have two different y-values that corresponds to the x-value of 1.
Therefore, the set that doesn't define a function is: {(1,3),(5,2),(6,9),(1,12),(10,2)} (last option).
Learn more about function on:
https://brainly.com/question/25638609
#SPJ1
A set of ordered pairs defines a function if each element of the domain is mapped to a single, unique value in the range. Set D does not define a function because it contains two distinct ordered pairs with the same first element, (1,3) and (1,12).
Explanation:A set of ordered pairs defines a function if each element of the domain is mapped to a single, unique value in the range. Looking at the given sets of ordered pairs, we can determine which ones define a function by checking if there are any repeated first elements in the pairs. If there are repeated first elements, then the set does not define a function.
Set A: {(−1,4),(0,4),(1,4),(2,4),(3,4)}Set B: {(1,2),(5,6),(6,7),(10,11),(13,14)}Set C: {(1,1),(2,2),(3,3),(4,4),(5,5)}Set D: {(1,3),(5,2),(6,9),(1,12),(10,2)}Out of these sets, Set D does not define a function because it contains two distinct ordered pairs with the same first element, (1,3) and (1,12).
factor X^3-7x^2-5x+35 by grouping. What is the resulting expression
Answer:
(x-7) (x^2-5)
Step-by-step explanation:
x^3-7x^2-5x+35
Factor out an x^2 from the first two terms and -5 from the last 2 terms
x^2 (x-7) -5(x-7)
Factor out (x-7)
(x-7) (x^2-5)
Answer:
(x - 7) (x^2 - 5)
Step-by-step explanation:
Factor the following:
x^3 - 7 x^2 - 5 x + 35
Factor terms by grouping. x^3 - 7 x^2 - 5 x + 35 = (x^3 - 7 x^2) + (35 - 5 x) = x^2 (x - 7) - 5 (x - 7):
x^2 (x - 7) - 5 (x - 7)
Factor x - 7 from x^2 (x - 7) - 5 (x - 7):
Answer: (x - 7) (x^2 - 5)
Pamela on average serves an ace 44% of the time. If she attempts 25 serves in her next games how many cases would you expect her to have
Answer:
[tex]11\ aces[/tex]
Step-by-step explanation:
we know that
Pamela on average serves an ace 44% of the time
That means ----> Pamela serves 44 aces every 100 serves
Using proportion
Let
x -----> the number of aces
[tex]\frac{44}{100}=\frac{x}{25}\\ \\x=44*25/100\\ \\x= 11\ aces[/tex]
Which expression is the factored form of −1.5w+7.5 ?
a) 1.5(5+w)
b) 1.5(w−5)
c) −1.5(w−5)
d) −1.5(w+5)
Answer:
c.
Step-by-step explanation:
the most that can be factored out is -1.5,
-1.5 * w = -1.5w
-1.5 * -5 = 7.5
-1.5w + 7.5, so it's
-1.5(w-5)